Difficulties in poetry translation - Maksud Mamatkulovich Temirov (UPT P2M Politeknik Negeri Malang, 2012)
Poetry is a separate world where the feelings of a poet and his or her heartfelt expressions reside. By means of the correspondence of meaning, word choice, rhyme, rhythm, and some other poetic devices in the poem a poet intends to express his or her ideas of a certain thing or a situation, experiences they or other people had, humane feelings such as love, revulsion, admiration, friendship, faith as well as descriptions of certain things or some circumstances they may experience. Poems could be written in different languages throughout the world but they carry certain meanings and purposes which are tended to be universally understood regardless which language they were written in. Following some points proposed by Hariyanto (no date) the writers try to give examples how to translate English poems into Uzbek, especially in how to handle the translation from the point of view of aesthetic values, expressive values, collocation, poetic structure, metaphorical expression, sounds. Indonesian translation is sometimes used to make the points clear.